Luteal and placental function in the bitch: spatio-temporal changes in prolactin receptor (PRLr) expression at dioestrus, pregnancy and normal and induced parturition - Hoffmann Bernd; Guscetti Franco; Boos Alois; Gram Aykut; Michel Erika; Kowalewski Mariusz P; Aslan Selim; Reichler Iris (BMC, 2011)
Abstract Background Endocrine mechanisms governing canine reproductive function remain still obscure. Progesterone (P4) of luteal origin is required for maintenance of pregnancy. Corpora lutea (CL) are gonadotrop-independent during the first third of dioestrus; afterwards prolactin (PRL) is the primary luteotropic factor. Interestingly, the increasing PRL levels are accompanied by decreasing P4 concentrations, thus luteal regression/luteolysis occurs in spite of an increased availability of gonadotropic support. PRL acts through its receptor (PRLr), the expression of which has not yet been thoroughly investigated at the molecular and cellular level in the dog. Methods The expression of PRLr was assessed in CL of non-pregnant dogs during the course of dioestrus (days 5, 15, 25, 35, 45, 65 post ovulation; p.o.) as well as in CL, the utero/placental compartments (Ut/Pl) and interplacental free polar zones (interplacental sites) from pregnant dogs during the pre-implantation, post-implantation and mid-gestation period of pregnancy and during the normal and antigestagen-induced luteolysis. Expression of PRLr was tested by Real Time PCR, immunohistochemistry and in situ hybridization. Results In non-pregnant CL the PRLr expression was significantly upregulated at day 15 p.o. and decreased significantly afterwards, towards the end of dioestrus. CL of pregnancy showed elevated PRLr expression until mid gestation while prepartal downregulation was observed. Interestingly, placental but not interplacental expression of PRLr was strongly time-related; a significant upregulation was observed towards mid-gestation. Within the CL PRLr was localized to the luteal cells; in the Ut/Pl it was localized to the fetal trophoblast and epithelial cells of glandular chambers. Moreover, in mid-pregnant animals treated with an antigestagen, both the luteal and placental, but not the uterine PRLr were significantly downregulated. Conclusions The data presented suggest that the luteal provision of P4 in both pregnant and non-pregnant dogs may be regulated at the PRLr level. Furthermore, a role of PRL not only in maintaining the canine CL function but also in regulating the placental function is strongly suggested. A possible functional interrelationship between luteal P4 and placental and luteal PRLr expression also with respect to the prepartal luteolysis is implied.